The limits of transparency: A systems theory view. (15th May 2019) - Valentinov, Vladislav; Verschraegen, Gert; Van Assche, Kristof
Abstract: The paper explores the implications of Ludwig von Bertalanffy's general systems theory for the current debates on the nature of organizational transparency as an element of good governance. If transparency implies the exchange of information, then it may be taken, at a metaphorical level, to constitute a dimension of metabolism theorized by Bertalanffy's open systems model. Yet, the model likewise lays bare some of the limits of transparency idea. Bertalanffy's work on the nature of emergent properties, his critique of the stimulus–response scheme, and his perspectivistic account of the systemic perception of the environment all point in the direction of the impossibility of full transparency. Later systems‐theoretic work on operational closure and self‐referentiality has reinforced and even radicalized these insights, which are shown to resonate with some of the key arguments in the contemporary economics, sociology of knowledge, and business ethics.